2011
DOI: 10.5142/jgr.2011.35.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Powder in the Treatment of Melasma: An Uncontrolled Observational Study

Abstract: Exposure to the sun, ultraviolet radiation, and oxidative stress are the chief etiologic factors responsible for melasma. The ingredients of Korean red ginseng powder, which include ginsenoside and phenolic compounds, have antioxidative effects and reduce ultraviolet B-induced pigmentation. This study was designed to evaluate the effectiveness and safety of Korean red ginseng powder in patients with melasma. In 25 female patients, 3 g of Korean red ginseng powder was orally administered for a 24 week period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Several studies have reported the melanogenesis inhibitor, causing inhibition of melanin synthesis, from P. ginseng . However, these studies were conducted with well-known compounds such as cinnamic acid and phenolic compounds [ 19 , 20 , 21 , 22 , 23 , 24 ]. For this study, we isolated ginsenoside Rh6 and vina-ginsenoside R4 and R13, whose effects on melanogenesis have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the melanogenesis inhibitor, causing inhibition of melanin synthesis, from P. ginseng . However, these studies were conducted with well-known compounds such as cinnamic acid and phenolic compounds [ 19 , 20 , 21 , 22 , 23 , 24 ]. For this study, we isolated ginsenoside Rh6 and vina-ginsenoside R4 and R13, whose effects on melanogenesis have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The mean level of pigmentation and erythema levels also decreased. In addition, 74% of the patients showed some improvement on the patient- and investigator-rated global improvement scales [44] .…”
Section: Effects Of Ginseng and Its Components On Melanogenesismentioning
confidence: 99%
“…Table 1 summarizes the direct effects of ginseng and its components on skin color and key enzymes involved in melanogenesis. Song et al reported that red ginseng powder improved melasma in a human clinical trial [44] . They orally administered Korean Red Ginseng powder for 24 weeks to female patients with melasma.…”
Section: Effects Of Ginseng and Its Components On Melanogenesismentioning
confidence: 99%
“…Exposure to ultraviolet (UV) radiation is the primary extrinsic factor that drives skin aging, which leads to the development of fine lines, wrinkles, and discoloration . Orally administered essential micronutrients, plant extracts, and marine‐based components have been studied for their effects on photoaged skin . Dietary intake of and supplementation with these nutrient and non‐nutrient ingredients can positively affect the skin's appearance by providing photoprotection from UV radiation and reducing oxidative stress and inflammation .…”
Section: Introductionmentioning
confidence: 99%